The cAMP-Dependent Protein Kinase Inhibitor H-89 Attenuates the Bioluminescence Signal Produced by Renilla Luciferase - Herbst, Katie J.; Allen, Michael D.; Zhang, Jin (PLOS ONE, 2009)
Background Investigations into the regulation and functional roles of kinases such as cAMP-dependent protein kinase (PKA) increasingly rely on cellular assays. Currently, there are a number of bioluminescence-based assays, for example reporter gene assays, that allow the study of the regulation, activity, and functional effects of PKA in the cellular context. Additionally there are continuing efforts to engineer improved biosensors that are capable of detecting real-time PKA signaling dynamics in cells. These cell-based assays are often utilized to test the involvement of PKA-dependent processes by using H-89, a reversible competitive inhibitor of PKA. Principal Findings We present here data to show that H-89, in addition to being a competitive PKA inhibitor, attenuates the bioluminescence signal produced by Renilla luciferase (RLuc) variants in a population of cells and also in single cells. Using 10 µM of luciferase substrate and 10 µM H-89, we observed that the signal from RLuc and RLuc8, an eight-point mutation variant of RLuc, in cells was reduced to 50% (±15%) and 54% (±14%) of controls exposed to the vehicle alone, respectively. In vitro, we showed that H-89 decreased the RLuc8 bioluminescence signal but did not compete with coelenterazine-h for the RLuc8 active site, and also did not affect the activity of Firefly luciferase. By contrast, another competitive inhibitor of PKA, KT5720, did not affect the activity of RLuc8. Significance The identification and characterization of the adverse effect of H-89 on RLuc signal will help deconvolute data previously generated from RLuc-based assays looking at the functional effects of PKA signaling. In addition, for the current application and future development of bioluminscence assays, KT5720 is identified as a more suitable PKA inhibitor to be used in conjunction with RLuc-based assays. These principal findings also provide an important lesson to fully consider all of the potential effects of experimental conditions on a cell-based assay readout before drawing conclusions from the data.